2017
DOI: 10.4269/ajtmh.16-0351
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pleuropulmonary Paragonimiasis Caused by Paragonimus mexicanus Treated as Tuberculosis in Ecuador

Abstract: A 30-year-old male, from a subtropical region of Ecuador, was hospitalized with a 5-year history of persistent cough with rusty brown sputum, chest pain, and progressive dyspnea. The patient underwent thoracic surgery 3 years ago for pleural effusion and subsequently received a 9-month regimen treatment of tuberculosis. However, there was no clinical resolution and symptoms became progressively worse. A chest radiograph and computerized tomography scan showed several small nodules in both lungs. Eggs of Parago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The sequence analysis of the PCR amplicons revealed that the amplified product was 461 bp (without primer sequences). The sequences obtained were identical to those previously obtained P. mexicanus metacercariae (DDBJ/EMBL/GenBank accession number: AB308377) and eggs (AB308378) occurring in Ecuador [ 14 ]. Therefore, the nucleotide sequence obtained in this study has been deposited as the metacercarial stage of P. mexicanus in the DDBJ/EMBL/GenBank database under the accession number LC317061.…”
Section: Resultssupporting
confidence: 64%
“…The sequence analysis of the PCR amplicons revealed that the amplified product was 461 bp (without primer sequences). The sequences obtained were identical to those previously obtained P. mexicanus metacercariae (DDBJ/EMBL/GenBank accession number: AB308377) and eggs (AB308378) occurring in Ecuador [ 14 ]. Therefore, the nucleotide sequence obtained in this study has been deposited as the metacercarial stage of P. mexicanus in the DDBJ/EMBL/GenBank database under the accession number LC317061.…”
Section: Resultssupporting
confidence: 64%
“…However, the clinical findings in paragonimiasis may resemble those of pleu-ropulmonary tuberculosis (TB), pneumonia, bronchitis, or bronchiectasis. Several studies reported paragonimiasis mimicking TB and the cases were misdiagnosed and treated as TB[ 7 , 8 ]. The mass in the pleural cavity that forms after standard treatment as our case can also lead to a misdiagnosis as malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms include fever and respiratory involvement, and most persons have a productive cough with rusty sputum or chest pain that can last from a few months to years. Thus, tuberculosis is the main condition to be ruled out in differential diagnosis (6,7). We report a public health intervention for a cluster of paragonimiasis observed during the end of 2021-May 2022, in San Lorenzo, Ecuador.…”
mentioning
confidence: 99%
“…The main trematode species known to cause paragonimiasis in Ecuador is P. mexicanus, although molecular characterization has not been performed extensively. Thus, information about circulating species might be incomplete (5,6).…”
mentioning
confidence: 99%